Results of a UK National Cancer Research Institute Phase II study of brentuximab vedotin using a response‐adapted design in the first‐line treatment of patients with classical Hodgkin lymphoma unsuitable for chemotherapy due to age, frailty or comorbidity (BREVITY). (14th September 2020) - Gibb, Adam; Pirrie, Sarah J.; Linton, Kim; Warbey, Victoria; Paterson, Kathryn; Davies, Andrew J.; Collins, Graham P.; Menne, Tobias; McKay, Pamela; Fields, Paul A.; Miall, Fiona M.; Nagy, Eszter; et al.
Summary: Standard treatment for classical Hodgkin lymphoma (cHL) is poorly tolerated in older patients and results disappointing. We assessed safety and efficacy of brentuximab vedotin (BV), in previously untreated patients with cHL unfit for standard treatment due to age, frailty or comorbidity. The primary outcome was complete metabolic response (CMR) by positron emission tomography/computed tomography after four BV cycles (PET4). The secondary outcomes included progression‐free survival (PFS), overall survival (OS), and toxicity. In all, 35 patients with a median age of 77 years and median total Cumulative Illness Rating Scale for Geriatrics (CIRS‐G) score of 6 were evaluable for toxicity and 31 for response. A median of four cycles were given (range one–16). In all, 14 patients required dose reduction due to toxicity and 11 patients stopped treatment due to adverse events (AEs). A total of 716 AEs were reported, of which 626 (88%) were Grade 1/2 and 27 (77%) patients had at least one AE Grade ≥3. At PET4, CMR was 25·8% [95% confidence interval (CI) 13·7–42.2%] and objective response rate 83·9% (95% CI 63·7–90·8%). Median PFS was 7·3 months (95% CI 5·2–9·0), and OS 19·5 months. Our results suggest that BV monotherapy is tolerable but suboptimal in the front‐line therapy of elderly or comorbid patients with cHL. Combining BV with other agents may be more effective. Trial Registration: Clinicaltrials.gov identifier: NCT02567851.